2017
DOI: 10.1007/s10157-017-1443-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined cyclosporine and prednisolone therapy using cyclosporine blood concentration monitoring for adult patients with new-onset minimal change nephrotic syndrome: a single-center pilot randomized trial

Abstract: The combination treatment regimen of ME-CyA and PSL with C2 >600 ng/ml has potential to be an important treatment option for adult new-onset MCNS patients. However, after ME-CyA dosage reduction and discontinuation, the relapse rate increased. It is thus necessary to establish a better dose-reduction method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Several RCTs examined the use of CNIs compared to glucocorticoids alone in adults with MCD and NS. 331,341,342 The quality of the evidence for these RCTs is low because there are concerns of serious risk of bias because of various study limitations and serious imprecision, as there are only a few studies, with a low number of participants (Supplementary Table S27 317,331,[341][342][343] ). These RCTs did not report critical clinical outcomes, all-cause mortality, or kidney failure.…”
Section: Key Informationmentioning
confidence: 99%
“…Several RCTs examined the use of CNIs compared to glucocorticoids alone in adults with MCD and NS. 331,341,342 The quality of the evidence for these RCTs is low because there are concerns of serious risk of bias because of various study limitations and serious imprecision, as there are only a few studies, with a low number of participants (Supplementary Table S27 317,331,[341][342][343] ). These RCTs did not report critical clinical outcomes, all-cause mortality, or kidney failure.…”
Section: Key Informationmentioning
confidence: 99%
“…Meanwhile relapses in MCD are more frequent and often occur during GC reduction. Recent findings have also shown that when treated with steroids alone, the recurrence rate can be as high as 60% in 3 months [24]. Taken together, it could be speculated that a response to prior infection such as influenza caused the development of GBM nephritis and MCD simultaneously.…”
Section: Discussionmentioning
confidence: 98%
“…There have been few studies on cyclosporine (CsA) monotherapy in adult MCD. Shirai et al [ 54 ] conducted a pilot open-label RCT in Japanese adults ( n = 21) with new-onset MCD. Adult new-onset MCD patients were initially treated with prednisolone (0.8 mg/kg) and 2 weeks after achieving proteinuria ≤1 g/day were randomized to CsA (2 mg/kg, goal CsA C2 level 600–1,200 ng/mL) with steroid taper by 4 months versus a prolonged prednisolone taper over 18 months.…”
Section: Steroid Minimization Approaches: Induction Of Remissionmentioning
confidence: 99%